Structural and Chemical Analysis of the Zirconia–Veneering Ceramic Interface. (January 2016) - Inokoshi, M.; Yoshihara, K.; Nagaoka, N.; Nakanishi, M.; De Munck, J.; Minakuchi, S.; Vanmeensel, K.; Zhang, F.; Yoshida, Y.; Vleugels, J.; Naert, I.; Van Meerbeek, B.
The interfacial interaction of veneering ceramic with zirconia is still not fully understood. This study aimed to characterize morphologically and chemically the zirconia–veneering ceramic interface. Three zirconia-veneering conditions were investigated: 1) zirconia–veneering ceramic fired on sandblasted zirconia, 2) zirconia–veneering ceramic on as-sintered zirconia, and 3) alumina–veneering ceramic (lower coefficient of thermal expansion [CTE]) on as-sintered zirconia. Polished cross-sectioned ceramic–veneered zirconia specimens were examined using field emission gun scanning electron microscopy (Feg-SEM). In addition, argon-ion thinned zirconia–veneering ceramic interface cross sections were examined using scanning transmission electron microscopy (STEM)–energy dispersive X-ray spectrometry (EDS) at high resolution. Finally, the zirconia–veneering ceramic interface was quantitatively analyzed for tetragonal-to-monoclinic phase transformation and residual stress using micro-Raman spectroscopy (µRaman). Feg-SEM revealed tight interfaces for all 3 veneering conditions. High-resolution transmission electron microscopy (HRTEM) disclosed an approximately 1.0-µm transformed zone at sandblasted zirconia, in which distinct zirconia grains were no longer observable. Straight grain boundaries and angular grain corners were detected up to the interface of zirconia– and alumina–veneering ceramic with as-sintered zirconia. EDS mapping disclosed within the zirconia–veneering ceramic a few nanometers thick calcium/aluminum-rich layer, touching the as-sintered zirconia base, with an equally thick silicon-rich/aluminum-poor layer on top. µRaman revealed t -ZrO2 -to- m -ZrO2 phase transformation and residual compressive stress at the sandblasted zirconia surface. The difference in CTE between zirconia– and the alumina–veneering ceramic resulted in residual tensile stress within the zirconia immediately adjacent to its interface with the veneering ceramic. The rather minor chemical elemental shifts recorded in the veneering ceramic did not suffice to draw definitive conclusions regarding potential chemical interaction of the veneering ceramic with zirconia. Sandblasting damaged the zirconia surface and induced phase transformation that also resulted in residual compressive stress. Difference in CTE of zirconia versus that of the veneering ceramic resulted in an unfavorable residual tensile stress at the zirconia–veneering ceramic interface.